(untitled) (American Journal of Pedagogical and Educational Research, 2023)
About 0.5 million new cases of the disease are registered annually in the world. Moreover, the higher the standard of living in the country, the more often doctors diagnose "Chronic heart failure" (CHF). Its frequency increases markedly with age. However, at any age, CHF requires treatment. And although it is extremely difficult to achieve full recovery, timely and correct therapy not only prolongs life, but also gives a person active longevity. One of the components of this therapy is non–drug treatment.